MICROBIAL CONTAMINATION AND BIOACTIVE COMPOUNDS OF JAMU BERAS KENCUR - Gunardi, Wani Devita; Teiseran, Virginia Marsella; Timotius, Kris Herawan (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Background: Jamu Beras Kencur (JBK) is recognized as an herbal medicine, containing two main components: the rhizome of Kaempferia galanga and rice. While previous research has identified bioactive compounds in galangal rhizomes, such as Ethyl p-Methoxycinnamate (EPMC), Ethyl-cinnamate, and Kaempferol, there are few reports on polar or aqueous compounds in JBK. LC-MS/MS and GC-MS enable comprehensive analysis of bioactive compounds, with LC-MS/MS detecting non-volatile, polar, and thermally sensitive compounds like flavonoids and glycosides, while GC-MS analyzes volatile and semi-volatile compounds, such as terpenoids, providing precise separation and identification. Therefore, this study were to know the amount and the growth of contaminant bacteria, yeast and mold; to determine the main bioactive compounds in JBK; and to determine the bioactive compound in aqueous and ethanolic extracts of rhizome that analysed with LC-MS/MS and GC-MS. Methode: JBK samples were sourced from local producers in West Jakarta, freshly prepared, and immediately analyzed for microbial contamination and bioactive compounds. Result: The analysis revealed microbial contamination in JBK, including Escherichia coli, Staphylococcus aureus, Coliform, yeast, and mold. Additionally, three novel flavonoid glycosides were identified: Chrysoeriol-4'-O-β-D-glucopyranoside, Patuletin-7-O-[6′′-(2-methylbutyryl)]-glucoside, and Acacetin-7-galactoside. Conclusion: Therefore, from the pharmacological perspective, JBK has the potentials as a healthy herbal drink. However, further preclinical and clinical studies are essential to validate its safety and efficacy for clinical use, which could pave the way for its integration into mainstream healthcare as a natural therapeutic option.